Traumatismo dentário em escolares de 8 a 12 anos do município de Pelotas - Goettems, Marília Leão (2012)
Traumatic dental injuries present a relatively high prevalence among children, may impact daily living and may require expensive treatments. Studies have shown controversial findings regarding risk factors for dental trauma, especially concerning the influence of socioeconomic conditions and behavioral and physical characteristics of the individuals, such as physical activity level and nutritional status. Thus, this theses aimed to systematically review literature regarding the effect of physical activity level and nutritional status on dental trauma occurrence; describe the methods of an oral health study with school children; and assess possible risk and protective factors for traumatic dental injuries in anterior permanent teeth of 8- to 12- years old children in Pelotas/RS. A randomized sample of 1,211 children was assessed in 20 public and private schools. Data collection included questionnaire applied to parents, to obtain socioeconomic variables and history of previous traumatic injury; interview with children, including demographic and behavioral characteristics; oral clinical examination of children to assess dental trauma occurrence (O´Brien) and collection of weight and height measures to obtain the body mass index (BMI). Data were entered twice in an EpiData 3.1 database and analyses were performed in Stata 10.0. Descriptive analysis was performed to obtain the prevalence of the dependent variable. Then, bivariate analyses were performed to test the association between dental trauma and independent variables. To investigate the independent effect of independent variables on dental trauma occurrence, Poisson regression analysis was performed, for the whole sample and by sex, estimating the Prevalence Ratio (PR) and respective confidence intervals (95% CI). The systematic review of literature showed that overweight/obesity may represent a risk factor for dental trauma occurrence; the effect of physical activity level was controversial and further studies using validated tools should investigate this association. In the epidemiological survey, dental trauma prevalence was 12.6% (CI 95% CI 10.8-14.7). In the adjusted analyses, boys had a higher risk than girls (RP 0.71; CI 95% 0.50-0.99). Older children (RP 3.57; CI 95% 1.73-7.34), with inadequate lip coverage (RP 2.03; CI 95% 1.22-3.38), and history of trauma in primary dentition (RP 2.60; CI 95% 1.80-3.75) had a higher prevalence of traumatic dental injuries. In a sex-stratified analysis, overweight/obese boys (RP 1.65; CI 95% 1.10-2.92) had higher risk of injuries. Results emphasize the need of preventive strategies to minimize dental trauma occurrence. Boys with inadequate BMI, as well as children with history of previous trauma had increased risk of dental trauma, suggesting the existence of accident-prone children